Direct Binding of Human Immunodeficiency Virus Type 1 Nef to the Major Histocompatibility Complex Class I (MHC-I) Cytoplasmic Tail Disrupts MHC-I Trafficking - Williams, Maya (American Society for Microbiology, 2002)
Nef, an essential pathogenic determinant for human immunodeficiency virus type 1, has multiple functions that include disruption of major histocompatibility complex class I molecules (MHC-I) and CD4 and CD28 cell surface expression. The effects of Nef on MHC-I have been shown to protect infected cells from cytotoxic T-lymphocyte recognition by downmodulation of a subset of MHC-I (HLA-A and -B). The remaining HLA-C and -E molecules prevent recognition by natural killer (NK) cells, which would otherwise lyse cells expressing small amounts of MHC-I. Specific amino acid residues in the MHC-I cytoplasmic tail confer sensitivity to Nef, but their function is unknown. Here we show that purified Nef binds directly to the HLA-A2 cytoplasmic tail in vitro and that Nef forms complexes with MHC-I that can be isolated from human cells. The interaction between Nef and MHC-I appears to be weak, indicating that it may be transient or stabilized by other factors. Supporting the fact that these molecules interact in vivo, we found that Nef colocalizes with HLA-A2 molecules in a perinuclear distribution inside cells. In addition, we demonstrated that Nef fails to bind the HLA-E tail and also fails to bind HLA-A2 tails with deletions of amino acids necessary for MHC-I downmodulation. These data provide an explanation for differential downmodulation of MHC-I allotypes by Nef. In addition, they provide the first direct evidence indicating that Nef functions as an adaptor molecule able to link MHC-I to cellular trafficking proteins.